Microbial phosphorus fluctuation in a hapludalf under natural pasture, with cut off and forage species introduction, fertilized in different times Amplitude no fósforo microbiano em um argissolo em pastagem nativa submetida à roçada e à introdução de espécies forrageiras com fertilização fosfatada em diferentes épocas - dos Santos Rheinheimer D. (2008)
In very weathered soils, the temporary phosphorus immobilization by soil microbial biomass (SMB) could be a mechanism to reduce P adsorption. This study was carried out to evaluate the microbial phosphorus (Pm) content fluctuation in a Hapludalf under natural pasture with cut off and exotic forage species introduction and fertilized with phosphorus fertilizers. The experiment was conducted in 1997 with five treatments: control without P, natural gafsa phosphate, triple superphosphate, triple superphosphate + lime, and single superphosphate + lime. In 2002, natural pasture was cut off and a mix of ryegrass and arrowleaf clover was planted in a no-tillage system. The original plots were split into three sub-plots: without P reapplication; P reapplication after cut off in winter, and P reapplication after cut off in spring. The first Pm evaluation was made 16 days before the first cut off, considered the beginning of the experiment (day 0). Soil samples for Pm evaluation were taken at 0, 25, 36, 55, 82, 111, 139, 163, 171, 181, 197, 219, 229, 248, 274, and 316 days after the beginning of the experiment. The cut off stimulated Pm immobilization by microbial biomass. Part of the phosphorus from fertilizers was temporary immobilized by microbial biomass.